Effect of shortening type on the rheological characteristics of cookie dough - Pakdaman Lahiji, Roghaieh; Mohammadi, Mehrdad; Moslemy, Masoumeh; Aminigram, Pooneh (Archives of Advances in Biosciences, 2013)
The effect of four types of shortening including a commercially vegetable oil (as control), palm olein (PO), palm stearin (PS), and a blend of the latter two oils with rapeseed oil (BF) on the rheological properties of cookie dough was determined by using dynamic oscillatory measurement testing. All of the obtained dough treatments showed weak liquid viscoelastic behavior. Their storage (G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–>) and loss (G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–>) moduli were almost the same with a loss tangent (tan δ) value of about 1. G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> was greater than G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> in most of the measured frequency range. Both G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> and G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> were frequency dependent and decreased with increasing of frequency. Differing oil compositions were found to differently affect on the overall strength of the doughs. The control dough showed the lowest frequency dependence. At lower frequencies, PO dough had the same consistency as the control, but at higher frequencies, its interaction was reduced leading to a weaker system. PS and BF doughs had stronger systems with higher values of G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> and G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> at low frequencies; both showed a dramatic drop in the values of G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> and G<!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–> at about 1 Hz. After this frequency, they showed similar rheological profile to the control. Baking test showed that the final quality of the baked products was significantly different in both appearance and internal texture.